Menstrual Abnormalities in Female International Students in Japan: Changes during Pre-Arrival, Difficult, and Current Periods - Yukie Matsuura; Yoko Abe; Yoshie Motoki; Nam Hoang Tran; Toshiyuki Yasui (MDPI AG, 2023)
The number of Japan's international students has rapidly increased in the last decade. This study examines the relationship between menstrual abnormalities in cycle and symptoms, stress level, and lifestyle of female international students in Japan across three time periods, namely pre-arrival, difficult, and current time periods. A cross-sectional design was employed, and data were collected through a self-administered questionnaire, including the menstrual distress questionnaire (MDQ), between December 2022 and February 2023. The questionnaire was distributed to 56 female international students from two universities in Japan, and a total of 29 valid responses were collected. We found varying menstrual cycle abnormalities and severity of menstrual symptoms across three time periods, with the difficult period after arrival in Japan displaying the highest symptom severity. Higher stress levels were significantly associated with more severe menstrual symptoms. Lifestyle habits such as alcohol consumption were also linked to menstrual symptoms. The current study emphasizes the importance of providing menstrual education, support, and resources to address international students' unique challenges in managing their menstrual health while studying abroad. By promoting awareness, education, and access to healthcare services, universities may contribute to international students' well-being and academic success.